Drosophila as a Model for Interorgan Communication: Lessons from Studies on Energy Homeostasis - Rajan, Akhila (2011)
Current studies of physiological communication between Drosophila organs are beginning to address the fundamental problem of how nutrients regulate organismal growth, stem cell behavior, immunity, and aging. Advances in the Drosophila genetic tool kit will allow the design of genetic screens to systematically identify factors involved in organ communication.